Palatal Rugae Pattern as an Aid for Personal Identification: A Forensic Study - R Kamala; Neha Gupta; Amol Bansal; Abhishek Sinha (Wolters Kluwer Medknow Publications, 2011)
Introduction Rugoscopy or palatoscopy is the study of palatal rugae in order to establish a person's identity. Rugae are protected from trauma as they are insulated from heat by tongue and buccal pad of fat, unlike fingerprints or lip prints that can get destroyed. Aims and objectives: This study was aimed to compare the rugae patterns in males and females of different age groups of Lucknow city, including twins, siblings and their parents. Effects of various dental treatment modalities on rugae pattern were also assessed. The uniqueness of palatal rugae as an aid for personal identification was the sole objective of this study. Materials and methods: A total of 1000 subjects were enrolled in the study and divided into five groups according to their age. Number, size and shape of rugae were recorded and compared according to Kapali et al. Conclusion: No two palates are alike in their configuration and once formed, they do not undergo any changes except in length due to normal growth, remaining in the same position throughout a person's entire life. Thus, palatal rugae appear to possess the features of an ideal forensic identification parameter, i.e. uniqueness, postmortem resistance and stability, provided antemortem record exists.